(untitled) (Journal of Fatima Jinnah Medical University, 2022)
Type 2 diabetes is classically associated with insulin resistance stemming from obesity along with relative pancreatic dysfunction to sustain this resistance.1 In the recent past, Scandinavian researchers highlighted that a considerable proportion of type 2 diabetics are actually insulin deficient out of proportion to their insulin resistance.2 These patients were younger, had low BMI, and more deranged glycemic control. Based on sophisticated tests measuring insulin secretion and resistance, high glycemia in this group was attributed more towards decreased insulin secretion instead of insulin resistance. This was described Cluster 2 or severe insulin deficiency diabetes (SIDD) in ANDIS data.2 This data changed the perception about solitary attribute of insulin resistance in pathophysiology of type 2 diabetes, and the way we treat them on ameliorating insulin resistance predominantly. (continue reading on PDF file....)